DNA accelerates the protease inhibition of a bacterial serpin chloropin - Xu, Jiawei; Ye, Wei; Yang, Ting Ting; Yan, Teng; Cai, Haiyan; Zhou, Aiwu; Yang, Yufeng (Frontiers in Molecular Biosciences, 2023)
Serine protease inhibitors (Serpins) are the most widely distributed protease inhibitors in nature and have been identified from all kingdoms of life. Eukaryotic serpins are most abundant with their activities often subject to modulation by cofactors; however, little is known about the regulation of prokaryotic serpins. To address this, here we prepared a recombinant bacteria serpin, termed chloropin, derived from green sulfur bacteria Chlorobium limicola and solved its crystal structure at 2.2 Å resolution. This showed a canonical inhibitory serpin conformation of native chloropin with a surface-exposed reactive loop and a large central beta-sheet. Enzyme activity analysis showed that chloropin could inhibit multiple proteases, such as thrombin and KLK7 with second order inhibition rate constants at 2.5×104 M−1s−1 and 4.5×104 M−1s−1 respectively, consistent with its P1 arginine residue. Heparin could accelerate the thrombin inhibition by ∼17-fold with a bell-shaped dose-dependent curve as seen with heparin-mediated thrombin inhibition by antithrombin. Interestingly, supercoiled DNA could accelerate the inhibition of thrombin by chloropin by 74-fold, while linear DNA accelerated the reaction by 142-fold through a heparin-like template mechanism. In contrast, DNA did not affect the inhibition of thrombin by antithrombin. These results indicate that DNA is likely a natural modulator of chloropin protecting the cell from endogenous or exogenous environmental proteases, and prokaryotic serpins have diverged during evolution to use different surface subsites for activity modulation.